Why Do Predicted Stock Issuers Earn Low Returns?. (22nd July 2022) - Lee, Charles M C; Li, Ken
Abstract: Predicted stock issuers (PSIs) are firms with expected high-investment and low-profit profiles that earn extremely low returns. We evaluate alternative explanations for this empirical phenomenon. Our results show top-PSI firms are cash-strapped, have lottery-like payoffs, high volatility, high beta, low liquidity, and high shorting costs. Over the next 2 years, top-PSI firms earn return on assets of −30% per year, report disappointing earnings, and experience strongly negative forecast revisions. They perform poorly in down markets and are six times more likely to delist for performance-related reasons. Overall, we find substantial support for mispricing, some support for nonstandard preferences, and virtually no support for the risk explanation. ( JEL G12, G14, G32, G40, G41) Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.